Cassava agronomy research and adoption of improved practices in Vietnam - Nguyen, Huu Hy; Nguyen, The Dang; Pham, Van Bien (International Center for Tropical Agriculture, 2001)
In the past few years, the economy of Vietnam has developed very rapidly, and in agriculture, food production has been quite successful, especially that of rice. At the same time cassava production has changed from being a crop providing food for humans to being a cash crop. The planting of new cassava varieties has increased the net income of farmers in some regions of Vietnam. In the area of agronomy, research conducted in some regions of the north and south of Vietnam had the objective of increasing cassava yields and income for the farmer, while maintaining the productivity of the soil. This included: - Soil research in South Vietnam showed that planting of cassava on the same land for many years reduced soil fertility more than with some other crops, trees or natural forest, resulting in soil degradation. - In fertilizer trials, the response of cassava depends on the type of soil and the kind of fertilizers. In both north and south Vietnam cassava showed strong responses to application of N and K, while there was a response to P in only one site. In long-term NPK trials conducted in Thai Nguyen University and in Hung Loc Center the application of 80:40:80 and 160:80:160 kg/ha of N-P2O5-K2O gave higher yields and higher economic returns than other treatments. - In intercropping trials conducted on research stations and on farmers’ fields with flat land, cassava intercropped with food crops and grain legumes increased income. In sloping areas cassava intercropping with peanuts or planting contour hedgerows of legume trees like Tephrosia candida or Gliricidia sepium reduced soil loss due to erosion and maintained or improved soil fertility. - In order to reduce the cost of production, the use of pre-emergence herbicides to control weeds was very effective and controlled about 90% of the weeds for the first 3-4 months after planting, resulting in higher profits than when cassava was weeded by hand or when post-emergence herbicides were applied.